2016
DOI: 10.3390/md14060116
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anti-Influenza A Virus Activity of 6′-amino-6′-deoxy-glucoglycerolipids Analogs

Abstract: A series of aminoglucoglycerolipids derivatives had been synthesized, including 6′-acylamido-glucoglycerolipids 1a–1f and corresponding 2′-acylamido-glucoglycerolipids 2a–2c bearing different fatty acids, glucosyl diglycerides 3a–3e bearing different functional groups at C-6′ and ether-linked glucoglycerolipids 4a–4c with double-tailed alkyl alcohol. The anti-influenza A virus (IAV) activity was evaluated by the cytopathic effects (CPE) inhibition assay. The results indicated that the integral structure of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
3
1
Order By: Relevance
“…Based on these considerations, three building blocks 2 – 4 (Scheme ) were designed. Compound 2 was synthesized from d -glucosamine according to a procedure reported by Ren et al, while compounds 3 and 4 were both prepared from ( S )-solketal. By applying appropriate functional group transformations to the free hydroxyl group on ( S )-solketal, we could either perform amide coupling as in the case of 3 or release the other two hydroxyl groups for acylation with fatty acids R 1 COOH and R 2 COOH to give 4 .…”
contrasting
confidence: 58%
“…Based on these considerations, three building blocks 2 – 4 (Scheme ) were designed. Compound 2 was synthesized from d -glucosamine according to a procedure reported by Ren et al, while compounds 3 and 4 were both prepared from ( S )-solketal. By applying appropriate functional group transformations to the free hydroxyl group on ( S )-solketal, we could either perform amide coupling as in the case of 3 or release the other two hydroxyl groups for acylation with fatty acids R 1 COOH and R 2 COOH to give 4 .…”
contrasting
confidence: 58%
“…A number of studies have reported a role for eEF2K in activating autophagy, largely using glioma cells, and also in breast cancer cell lines treated to induce endoplasmic reticulum stress [ 41 , 43 , 45 , 61 , 62 ]. This possibility ‘makes sense’ at several levels: eEF2K and autophagy are both negatively regulated by mTORC1; protein synthesis is a major user of amino acids that can be generated by autophagy; and eEF2K negatively regulates an anabolic process, so it would be logical that it positively regulates a catabolic one.…”
Section: Eef2k In Cancer Cell Survival: How Does Eef2k Promote Surmentioning
confidence: 99%
“…Among them, 203g showed the best activity with an IC 50 of 69.9 µM [ 90 , 91 ]. Later, new analogues 204 – 207 ( Figure 19 ) were prepared and tested for anti-IAV activity, and the authors concluded that acylamino and glycerol groups of the glycolipids were essential for the inhibitory activity on IAV multiplication [ 92 ]. From this new series, 204d was the most potent, with an IC 50 of 60.8 µM, and may provide a point of exploration of unique aminoglycoglycerolipids in drug discovery for pneumonia caused by viruses.…”
Section: Chemistry and Biology Of Glycoglycerolipidsmentioning
confidence: 99%